Mouvement du 20 février et appropriation de l’espace public au Maroc - Mohamed Naimi (Les Cahiers d’EMAM)
Throughout a case study of the February 20 Movement (M20F) in Morocco, this article aims to highlight the fact that political participation goes beyond electoral and partisan form and gradually integrates collective action protest deployed in public space / public spaces. In fact, this reality is supported by popular revolutions and uprisings of the “Arab Spring”: social movements have become key political actors in today’s civil, society especially in the Arab world since 2011. In Morocco, this is translated by the emergence of M20F. Certainly, the Moroccan Constitution of 2011, as the main response to the demands of the M20F, broadens the scope of political participation by giving associations and NGOs of civil society, new political roles in a participatory democracy. Nevertheless, it has neglected the role of social movements as an active component within a newly non-established civil society.